2008
DOI: 10.1177/147323000803600616
|View full text |Cite
|
Sign up to set email alerts
|

The Combination of Low-Dose Levobupivacaine and Fentanyl for Spinal Anaesthesia in Ambulatory Inguinal Herniorrhaphy

Abstract: This study investigated whether the addition of 25 microg intrathecal fentanyl to levobupivacaine spinal anaesthesia for outpatient inguinal herniorrhaphy allows a sub-anaesthetic levobupivacaine dose to be used. Forty patients were assigned to receive 5 mg levobupivacaine 0.5% mixed with 25 microg fentanyl (group LF) or 7.5 mg levobupivacaine 0.5% (group L). The highest sensory block levels achieved were T7 (range T5 - T9) and T6 (range T4 - T9) in groups LF and L, respectively. The times to two-segment regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…The advantages of an awake patient, minimal drug costs, and rapid patient turnover has made this the method of choice for many surgical procedures. However, spinal anesthesia for hernia repair is more complicated; a higher level of sensory block is required, but increasing the dose of long-acting local anesthetics may produce extensive sensory and motor block as well as arterial hypotension, resulting in delayed discharge from hospital [5]. Ropivacaine and levobupivacaine are quite new among local anesthetics.…”
Section: Introductionmentioning
confidence: 98%
“…The advantages of an awake patient, minimal drug costs, and rapid patient turnover has made this the method of choice for many surgical procedures. However, spinal anesthesia for hernia repair is more complicated; a higher level of sensory block is required, but increasing the dose of long-acting local anesthetics may produce extensive sensory and motor block as well as arterial hypotension, resulting in delayed discharge from hospital [5]. Ropivacaine and levobupivacaine are quite new among local anesthetics.…”
Section: Introductionmentioning
confidence: 98%
“…Some studies with fentanyl were performed to reduce the dose of local anesthetic used for IHR. The addition of 25 µg intrathecal fentanyl to low-dose levobupivacaine (5 mg) or low dose bupivacaine (7.5 mg) provided an adequate quality of spinal anesthesia and postoperative pain relief 9,10 .…”
Section: Discussionmentioning
confidence: 99%
“…[64,65] Smaller doses with added adjuvants have been reported for ambulatory cases; in gynecological patients 3 mg along with 10 µg fentanyl may be used safely,[66] 5 or 7.5 mg 0.5% intrathecal levobupivacaine plus fentanyl 25 µg for ambulatory patients undergoing inguinal herniorraphy provides good quality spinal anaesthesia and minimizes the need for intra-operative analgesia. [67] In a double-blinded study Sanansilp et al [68] compared spinal isobaric or hyperbaric 0.42% levobupivacaine. They found that hyperbaric levobupivacaine spread higher than the isobaric form, suggesting that the former is more predictable.…”
Section: Drugs For Spinal Anaesthesiamentioning
confidence: 99%